1984
DOI: 10.2527/jas1984.583666x
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Resistance of Fecal Coliforms from Swine Fed Subtherapeutic and Therapeutic Levels of Chlortetracycline2

Abstract: The effect of feeding subtherapeutic (27.5 micrograms/g of diet for 85 d) and therapeutic (220 micrograms/g of diet for 14 d, followed by an antibiotic-free diet for 71 d) levels of chlortetracycline (CTC) on the antibiotic resistance of fecal coliforms of pigs from two herds (36 pigs/herd) with different histories of antibiotic exposure when housed in a newly constructed confinement facility was determined. The CTC-resistant coliforms were higher (65 vs 51%) for antibiotic (AB) pigs than for nonantibiotic (NA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0

Year Published

1988
1988
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 6 publications
1
31
0
Order By: Relevance
“…Food animal production consumes large amounts of antimicrobial drugs and thus can serve as an important arena for emergence and maintenance of AR (1,3,46). Nevertheless, it is not clear that eliminating all nontherapeutic antimicrobial use in animal production will result in a significant reduction in the prevalence of AR bacteria (7,10,24,25,37,41). This is because many factors unrelated to antimicrobial use are also implicated in the increase in prevalence of AR, including animal stress (30,31), close linkage to other selectively advantageous genes (2,9,16,21), plasmid addiction (14,17), and secondary advantage conveyed by the AR genes (15,27,36).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Food animal production consumes large amounts of antimicrobial drugs and thus can serve as an important arena for emergence and maintenance of AR (1,3,46). Nevertheless, it is not clear that eliminating all nontherapeutic antimicrobial use in animal production will result in a significant reduction in the prevalence of AR bacteria (7,10,24,25,37,41). This is because many factors unrelated to antimicrobial use are also implicated in the increase in prevalence of AR, including animal stress (30,31), close linkage to other selectively advantageous genes (2,9,16,21), plasmid addiction (14,17), and secondary advantage conveyed by the AR genes (15,27,36).…”
Section: Discussionmentioning
confidence: 99%
“…One strategy to decrease the prevalence of AR bacteria is to discontinue using antimicrobial drugs for growth promotion and prophylaxis in food animals (4,11,22,43,44). Unfortunately, this strategy has produced mixed results that are dependent on the duration and amount of antimicrobial drug use (10,16,24,25,37,38,41). While pathogenic bacteria are the primary concern, commensal bacteria are an important reservoir for AR genes.…”
mentioning
confidence: 99%
“…Our findings concerning antimicrobial susceptibility and the intervention agree with earlier studies where removal of antimicrobial agents from cattle management resulted in increased susceptibility in enteric bacteria (1) and in another study where increasing calf exposure to penicillin in milk was associated with decreasing susceptibility (24). In an early study using therapeutic and subtherapeutic levels of chlortetracycline in swine feed, investigators found that feeding subtherapeutic levels of chlortetracycline (27.5 g/g feed) for longer periods (84 days) decreased Tet susceptibility in fecal coliforms in comparison to using therapeutic levels (220 g/g feed) for shorter periods (14 days) and that susceptibility increased after therapeutic levels were discontinued (25). The finding that oxytetracycline use in adult cattle decreased the risk of susceptibility in the herd level multivariable analysis also supports the theory that drug resistance will be sustained in the presence of selective pressure (26).…”
Section: Discussionmentioning
confidence: 99%
“…In 1969, the Swann report published in Great Britain, recommended the exclusion of the antimicrobial agents from animal feed that were used in human and/or animal therapy (Swann, 1969). Numerous studies described the effect of long-term usage of subtherapeutic doses of tetracyclines resulting in the increased level of resistant gut bacteria or pathogens (Smith and Tucker, 1975;Hooper and Hirsh, 1977;Langlois et al, 1984;Hinton et al, 1985). In contrast to the United States, the application of tetracyclines as growth promoters is not allowed neither in the European Union nor in the Czech Republic (Council Directive 70/524 EEC, 1970;Prescott et al, 2000), and since 1975, no tetracycline has been used for the growth promotion in Europe (Schwarz and Chaslus-Dancla, 2001).…”
Section: Applications Of Tetracyclines In Veterinary Medicinementioning
confidence: 99%